A disseminação da informação face a uma abordagem hipertextual, um estudo de caso na PRODABEL - Carlos Henrique Rezende Falci (1997)
The hypertext presents itself as one among several new information technologies, emerged today. However, more than a simple technology, the hypertext can be seen as a new philosophy in dealing with information, organized in nodes and connected by links. At present, information explosion took plays and organizations have faced a dillema: how to coordinate globalized world pressures, which calls for a constant updated information, with an adequate identification of information requirements? This thesis intended to investigate hypertext as an adequate supporting tool in the process of disseminating information at the Prefeitura Municipal de Belo Horizonte. The philosophy and technical features of hypertextual systems revealed themselves appropriate once they allow users to access informational contents in an integrated way, by constructing conceptual networks, which agregate a huge number of data.